Teacher Perceptions of Their Curricular and Pedagogical Shifts: Outcomes of a Project-Based Model of Teacher Professional Development in the Next Generation Science Standards - Shernoff, David J.; Sinha, Suparna; Bressler, Denise M.; Schultz, Dawna (Frontiers in Psychology, 2017)
In this study, we conducted a model of teacher professional development (PD) on the alignment of middle and high school curricula and instruction to the Next Generation Science Standards (NGSS), and evaluated the impact of the PD on teacher participants’ development. The PD model included a 4-day summer academy emphasizing project-based learning (PBL) in the designing of NGSS-aligned curricula and instruction, as well as monthly follow-up Professional Learning Community meetings (PLCs) throughout the year providing numerous opportunities for teachers to develop and implement lesson plans, share results of lesson writing and implementation (successes and challenges), provide mutual feedback, and refine curricula and assessments. Following the summer academy, six female teachers were interviewed about their current conceptualizations of NGSS, the extent of curricular shifts made that are required by NGSS, their self-perceptions regarding their level of accomplishment in curriculum writing, and the benefits of the PD in reaching their goals related to NGSS. Interviews were supplemented with an analysis of lesson plans written while participating in the PD program. The interviewed teachers suggested that they had made important conceptual and pedagogical shifts required by NGSS as they participated in the PD, and also noted a variety of challenges as they made this shift. While all teachers were relative novices at NGSS curriculum writing before the PD, most of the teachers interviewed felt that they had achieved the status of an “accomplished novice” following the summer academy. An analysis of their written lesson suggested a great range in the extent to which teachers effectively applied their understanding of NGSS to write lessons aligned to NGSS. Interviewed teachers believed that the PD model was helpful to their development as science teachers, and all reported that there were no aspects of the PD that were not helpful. Even though most teachers obtained a basic understanding and conceptualization of NGSS and PBL, their application of this understanding in their curriculum writing varied. The present study may help to inform future efforts to support teachers to align curricula and instruction to NGSS through teacher professional development.